A clinical Pseudomonas juntendi strain with blaIMP−1 carried by an integrative and conjugative element in China - Zheng, Lin; Zhang, Xinfang; Zhu, Lingwei; Lu, Gejin; Guan, Jiayao; Liu, Mingwei; Jing, Jie; Sun, Shiwen; Wang, Ying; Sun, Yang; Ji, Xue; Jiang, Bowen; et al. (Frontiers in Microbiology, 2022)
Objective To precisely determine the species of a carbapenem-resistant Pseudomonas strain 1809276 isolated from the urine of a Chinese patient and analyze its integrative and conjugative element (ICE) 1276 formation mechanism. Methods Single-molecule real-time (SMRT) sequencing was carried out on strain 18091276 to obtain the complete chromosome and plasmid (pCN1276) sequences, and average nucleotide identity (ANI) was used for precise species identification. The ICEs in GenBank with the same integrase structure as ICE 1276 were aligned. At the same time, the transfer ability of blaIMP−1 and the antibiotic sensitivity of Pseudomonas juntendi 18091276 were tested. Results This bacterium was P. juntendi, and its drug resistance mechanism is the capture of the accA4' gene cassette by the Tn402-like type 1 integron (IntI1-blaIMP−1) to form In1886 before its capture by the ΔTn4662a-carrying ICE 1276. The acquisition of blaIMP−1 confers carbapenem resistance to P. juntendi 18091276. Conclusion The formation of blaIMP−1-carrying ICE 1276, its further integration into the chromosomes, and transposition and recombination of other elements promote bacterial gene accumulation and transmission.